ESTABLISHMENT OF SCHOOL MEDICAL ROOM (UKS) IN ORDER TO IMPROVE THE HEALTH LEVEL OF STUDENTS AND TEACHERS AT MTS AND MAS AL-FATAH KABUPATEN MALANG - Ardhiani, Innas Tiara; Yulindahwati, Asworoningrum (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
School Medical Room (UKS) have an important role in instilling healthy living behavior and improving students' health through the implementation of the "Trias UKS" model, which includes Health Education, Health Services, and Healthy School Environment Development. As an effort to improve the quality of UKS implementation, schools are encouraged to achieve stratification standards ranging from minimal to optimal levels. However, the establishment of School Health Efforts (UKS) faces various challenges that can hinder its optimal implementation. These challenges include limited resources, both in terms of funding, facilities, and trained health workers. Suboptimal coordination between schools, health offices, and communities is also an obstacle to the alignment of sustainable health programs. However, if these challenges can be overcome, UKS has the potential to provide a significant long-term impact on the health of students and the school community. Increasing health awareness from an early age can form healthy living habits that are carried into adulthood. Realizing the importance of the existence of UKS in schools and the desire to form adolescents who are aware of health, the Poltekkes Kemenkes Malang initiated a community service program to establish UKS facilities at MTS and MAS Al-Fatah, Malang Regency, which previously did not have such facilities. This community service activity was carried out on August 10, 2024, involving training for representatives of local governments, health centers, teachers, and students, with a focus on the formation and management of UKS. The methods used included lectures, discussions, and interactive Q&A sessions guided by the committee. The main results of this activity were the formation of the UKS committee, the signing of an integrity pact, and the provision of essential medical equipment for UKS. Pre- and post-tests showed a significant increase in participant knowledge, with post-test scores reflecting a 50% increase in understanding. This program aims to empower school communities to manage health services independently and become a model for similar programs in other areas. The success of this initiative at MTS and MAS Al-Fatah is expected to inspire the development of UKS in other schools in Malang Regency. Keywords: Formation of UKS, UKS knowledge, UKS Al-Fatah Turen.